2021
DOI: 10.1155/2021/4547537
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Hartmann Reversal: A Case-Control Study

Abstract: Background. Laparoscopic reversal of Hartmann’s procedure (LHR) offers reduced morbidity compared with open Hartmann’s reversal (OHR). The aim of this study is to compare the outcome of laparoscopic versus open Hartmann reversal. Materials and Methods. Thirty-four patients who underwent Hartmann reversal between January 2017 and July 2019 were evaluated. Patients underwent either LHR (n = 17) or OHR (n = 17). Variables such as numbers of patients, patient’s age, sex, body mass index (BMI), comorbidities, ASA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…There have been fewer reports on HR from East Asia than from Western countries 1,6,7,11,12,16,17 . Additionally, the rate of HR in our study was lower (14.3%) than reported in previous studies from Western countries (21%–63%) 1,6,16 and East Asia (19%–44%) 7,18 .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…There have been fewer reports on HR from East Asia than from Western countries 1,6,7,11,12,16,17 . Additionally, the rate of HR in our study was lower (14.3%) than reported in previous studies from Western countries (21%–63%) 1,6,16 and East Asia (19%–44%) 7,18 .…”
Section: Discussioncontrasting
confidence: 82%
“…HP is often performed as an emergency operation, and in such cases, surgeons tend to prefer open HP (OHP) over laparoscopic HP (LHP) 12 . In HR, the previous surgical approach is an important factor to consider due to its effect on intra‐abdominal adhesions; however, there is no literature on the effect of the surgical approach in HP on the operative outcomes of LHR.…”
Section: Introductionmentioning
confidence: 99%
“…Mean operative time was 184.6±47.06min in our study and it corresponds well with the study conducted by Panaccio et al in the period between January 2017 and July 2019 in the department of medicine and oral sciences and biotechnologies, unit of general and oncology surgery, Casa Di Cura Pierangeli, University G. D'Annunzio, Chieti-Pescara, Italy in which mean operative time was 180.5±35.1 minutes in the LHR group. 16 In a review of other similar studies, operation time was the interval between the first skin incision and wound closure. Patients having short rectal stump, rectosigmoid colon cancer, and previous radiotherapy in the pelvis resulting in dense adhesions and fibrotic stricture of the rectal stump increase the operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that 6–35% of patients who undergo HP do not proceed to reversal, leading to a permanent stoma [ 4 , 14 17 ]. Horesh et al reported Hartmann's reversal rate of 57.6% when those who died within the perioperative 30 days after HP were excluded [ 18 ].…”
Section: Discussionmentioning
confidence: 99%